Heterogeneous circulating miRNA profiles of PBMAH - Hara, Kazunari; Murakami, Masanori; Niitsu, Yoshihiro; Takeuchi, Akira; Horino, Masato; Shiba, Kumiko; Tsujimoto, Kazutaka; Komiya, Chikara; Ikeda, Kenji; Tsuiki, Mika; Tanabe, Akiyo; Tanaka, Toshihiro; et al. (Frontiers in Endocrinology, 2022)
Objective: Primary bilateral macronodular adrenal hyperplasia (PBMAH), a rare cause of Cushing syndrome, is often diagnosed as a bilateral adrenal incidentaloma with subclinical cortisol production. Circulating microRNAs (miRNAs) are a characteristic of adrenocortical adenomas, but miRNA expression in PBMAH has not been investigated. We aimed to evaluate the circulating miRNA expression in patients with PBMAH and compare them with those in patients with non-functioning adrenocortical adenoma (NFA) and cortisol-producing adrenocortical adenoma (CPA). Methods: miRNA profiling of plasma samples from four, five, and five patients with NFA, CPA, and PBMAH, respectively, was performed. Selected miRNA expressions were validated using quantitative RT-PCR. Results: PBMAH samples showed distinct miRNA expression signatures on hierarchical clustering while NFA and CPA samples were separately clustered. PBMAH was distinguished from the adenoma group of NFA and CPA by 135 differentially expressed miRNAs. Hsa-miR-1180-3p, hsa-miR-4732-5p, and hsa-let-7b-5p were differentially expressed between PBMAH and adenoma (P = 0.019, 0.006, and 0.003, respectively). Furthermore, PBMAH could be classified into two subtypes based on miRNA profiling: subtype 1 with a similar profile to those of adenoma and subtype 2 with a distinct profile. Hsa-miR-631, hsa-miR-513b-5p, hsa-miR-6805-5p, and hsa-miR-548av-5p/548k were differentially expressed between PBMAH subtype 2 and adenoma (P = 0.027, 0.027, 0.027, and 1.53E-04, respectively), but not between PBMAH, as a whole, and adenoma. Conclusion: Circulating miRNA signature was identified specific for PBMAH. The existence of subtype-based miRNA profiles may be associated with the pathophysiological heterogeneity of PBMAH.